Perception of management innovation as a key factor in achieving competitive advantage in companies in Bosnia and Herzegovina - Mirela Kljajić-Dervić; Željko Mateljak; Ema Burić (Economic Review: Journal of Economics and Business, 2022)
Every company strives to achieve competitive advantage, which is why managers constantly seek new ways of reaching that goal. One of the best ways to gain competitive advantage is through innovation. In theory, innovation can be classified in numerous ways. Some of them include management innovation, which can simply be defined as the process of innovating what managers do. Despite the power of management innovation to propel a company to the level of excellence no other company can compete with, this research has showed that managers in Bosnia and Herzegovina (BiH) are not fully aware of its importance.
Keywords: 032; 330; management innovation; competitive advantage; Bosnia and Herzegovina